Contingent valuation of nonmarket benefits in project economic analysis a guide to good practice - Sajise, Asa Jose; Samson, Jindra Nuella G.; Quiao, Lotis; Sibal, Jasmin; Raitzer, David A.; Harder, Dieldre (Manila,Philippines Asian Development Bank, 2021)
Explains how to measure people's willingness to pay for goods and services, such as improved air quality, that are not traded in a market. This guide aims to help improve the assessment of potential investment projects.
Introduction - - Key Consideration When Planning a CVM Study - - Designing the Sampling Strategy - - Contingent Valuation Questionnaire: Best Practices and Design Issues - - Implementation of Contingent Valuation Surveys - - Managing and Analyzing CVM Data - - Future Directions for CVM Practice.
Keywords: Contingent valuation -- Economic aspects; Contingent valuation -- Government policy